(untitled) - Smith, John E. (Cambridge, U.K., 2004)
Biotechnology will undoubtedly be the major technology of the twenty-first century. It concerns the practical application of biological organisms or their various components to the benefit of humandkind, and spans a multitude of modern and traditional industries. The rise of genetic engineering, genomics, proteomics, and the creation of transgetic crops and animals has revolutionised activities as varied as brewing beer and the treatment of sewage and wastewater, or drug development and agriculture.
Khía cạnh xã hội của công nghệ sinh học
Keywords: Biotechnology